Inflammation in first‐episode psychosis: The contribution of inflammatory biomarkers to the emergence of negative symptoms, a systematic review and meta‐analysis. (5th March 2022) - Dunleavy, Connor; Elsworthy, Richard J.; Upthegrove, Rachel; Wood, Stephen J.; Aldred, Sarah
Abstract: Objective: To provide a comprehensive analysis of cytokine perturbations in antipsychotic‐naïve first‐episode psychosis (FEP) populations and assess the relationship between inflammatory biomarkers and negative symptom severity. Methods: A systematic review and meta‐analysis following PRISMA guidelines were conducted. A total of 1042 records were identified via systematic search of EMBASE, MEDLINE and APA PsycInfo databases. Sixteen studies met the inclusion criteria and were eligible for inclusion in the review. Ten of these studies had sufficient data for inclusion in a random effects, pooled‐effect meta‐analysis. Results: A significant and large effect size was reported for IFN‐γ, IL‐6 and IL‐12, and a moderate effect size reported for IL‐17 ( p = <0.05) in people with antipsychotic naive first episode psychosis, compared to healthy controls, suggesting a significant elevation in proinflammatory cytokine concentration. Non‐significant effect sizes were reported for TNF‐α, IL‐1β, IL‐2, IL‐4, IL‐8 and IL‐10 ( p = >0.05). Regarding proinflammatory cytokines and relationships to negative symptomology, moderate positive relationships were reported for negative symptoms and IL‐1β, IL‐2, IL‐6 and TNF‐α, across four studies. For anti‐inflammatory cytokines, one strong and one weak‐to‐moderate negative relationship was described for IL‐10 and negative symptoms. Contrastingly, a strong positive relationship was reported for IL‐4 and negative symptoms. Conclusion: There is evidence of significantly elevated proinflammatory cytokines in antipsychotic‐naïve FEP populations, alongside promising findings from cohort data suggesting an interaction between inflammation and primary negative symptomology. Future studies should seek to come to a consensus on a panel of cytokines that relate most specifically to negative symptoms, and consider longitudinal studies to investigate how cytokine fluctuations may relate to exacerbation of symptoms.